ANALISIS SEMIOTIKA ILLUSTRASI âKOALISI HIRUK-PIKUK CAPRES 2014â PADA MAJALAH TEMPO - Priyadi, Catur (Universitas Prof. Dr. Moestopo (Beragama), 2015)
Easily set up a press agency or office of preaching became one of the reasons some of the political elite to establish a news agency. In addition, the presence of motifs commercialism, some underlying political affiliation. Media TempoGrup apparently take advantage of the situation. Through the case of contradiction Cover Tempo 7 April 2014 could predict or forecast the presidential candidates who will qualify in the presidential whereas almost one month interval, then coupled with various symbols of mystery. Not Tempo otherwise create a sensation, but this time make public sensation became curious and tried to review it. who was then busy discussed, Tempo Magazine utilizing two big names Presidential Candidate, namely Prabowo Subiakto and Joko Widodo, as Tempo Magazine Cover 7 April 2014 through a news photograph, coupled with attention-grabbing headline âCoalition frenzy Candidates 2014â at Tempo Magazine, 7-13 April 2014 edition â. By using semotics analysis of Roland Barthes, the author seeks to uncover denotative, connotative, and myths behind the news photos. Not only interpret the photo, but the statement and title in the headline can also be interpreted using the same theory. It should be underlined that semiotics is the study of signs. Interpret more than just communication, but looking deeper into the meaning dikomunikasikannya. Semiotic analysis talking about the meaning as seen (denotation), the meaning behind what is visible (connotation), and myths